The cosmic perspective - Bennett, Jeffrey O. (Boston : Addison-Wesley, 2014)
"The story of modern astronomy and the new perspective that astronomy gives us of ourselves and our planet: the cosmic perspective"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Astronomy -- Textbooks